Public Attitudes toward Immigration - Jens Hainmueller; Daniel J. Hopkins (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
Immigrant populations in many developed democracies have grown rapidly, and so too has an extensive literature on natives' attitudes toward immigration. This research has developed from two theoretical foundations, one grounded in political economy, the other in political psychology. These two literatures have developed largely in isolation from one another, yet the conclusions that emerge from each are strikingly similar. Consistently, immigration attitudes show little evidence of being strongly correlated with personal economic circumstances. Instead, immigration attitudes are shaped by sociotropic concerns about national-level impacts, whether those impacts are cultural or economic. This pattern of results has held up as scholars have increasingly turned to experimental tests, and it fits the evidence from the United States, Canada, and Western Europe. Still, more work is needed to strengthen the causal identification of sociotropic concerns and to isolate precisely how, when, and why they matter for attitude formation.
Keywords: 330; immigration attitudes; political economy; political psychology; prejudice; cultural threat; public opinion